Directions in Music: Stakeholder Perspectives on Blockchain Innovations in Music Streaming - Lovett, Matthew (Frontiers in Blockchain, 2020)
Abstract In its various guises, blockchain technology has generated friction across a range of sectors; most notably as an enabler of anonymous trading, but perhaps more significantly in terms of longer-term adoption, via its application in supply-chain monitoring, and rights management. This article draws on stakeholder theory to examine the deployment of blockchain technology in the music streaming sector, in order to assess how these blockchain-based innovations - via interactions with users, market environments, and overarching economic and political frameworks - are contributing to evolving conceptions of ownership, inclusion and involvement. Initially, the article examines three approaches to theorising and designing inclusive governance structures that acknowledge the distributed, and at times collaborative, nature of interaction between members of a group; be that a society, a company or other form of organised grouping. Here I draw on three discourses to underpin the evolving role that stakeholders - in the guise of networks, companies, societies and platforms – can play in digital commerce: (i) John Rawls’ concept of Distributive Justice, (ii) a set of principles known as the ‘Scandinavian approach to Participatory Design’; and (iii) the emergent concept of ‘New Economics’, a term particularly associated with current and emergent left-wing political perspectives in the UK. Taking three use cases in Resonate, Musicoin and Choon, the article engages with how blockchain-based music start-ups are interacting with an evolving marketplace; identifying the benefits and beneficiaries of blockchain uptake, along with a wider set of structural changes that are taking place within music commerce. The article focuses on music streaming in particular to explore how blockchain is transforming the way that things are owned, and how it is contributing to an evolving conception of ownership, and reflects on how blockchain is finding increased used within the physical world of private and public property, and political governance. The article concludes by considering how stakeholders with the music streaming sector are indicative of wider changes, challenges and tensions within the digital marketplace, and the role that innovations in blockchain can play in this transition.